Unique Running Pattern and Mucosal Morphology Found in the Colon of Cotton Rats - Chuluunbaatar, Tsolmon; Ichii, Osamu; Nakamura, Teppei; Irie, Takao; Namba, Takashi; Islam, Md Rashedul; Otani, Yuki; Masum, Md Abdul; Okamatsu-Ogura, Yuko; Elewa, Yaser Hosny Ali; Kon, Yasuhiro (Frontiers in Physiology, 2020)
Cotton rats are one of the experimental rodents used for testing different infectious and noninfectious diseases, including gastrointestinal tract pathology. However, their intestinal morphological characteristics are still poorly understood. Here, we clarified the anatomical and histological characteristics of the cecum and ascending colon (AC) of young (1–3-month old), adult (4–6-month-old), and old (10–12-month-old) cotton rats. The large intestine (LI) in cotton rats is composed of the cecum, AC, transverse and descending colons, and rectum, and is similar to that of other mammals. The AC begins with a double or triple spiral loop-like flexure (SLLF) and finishes with a coupled horseshoe-like flexure (HSLF). A single longitudinal mucosal fold (SLMF) was found at the beginning of the AC along the mesentery line and developed with age. Further, the SLMF contained several numbers of lymphatic nodules (LNs) indicating their role in digestive and immunological functions. Small and large protuberant LNs were found in the cecum and SLLF, respectively, whereas thin and flat LNs were observed in the HSLF and transverse colon, respectively. In sex-related differences, adult females had a significantly longer AC with a higher number of SLLF compared to that in males. The SLMF length and LN number were also longer and higher in adult females, respectively, compared to those in adult males. These are crucial findings indicating the presence of sex-related differences in the morphology of the LI in cotton rats and ours is the first study to discover a sex difference in the mammalian LI lining. Our study clarified the unique morphology of the LI in cotton rats, which could serve as the principal model for elucidating species-specific digestive tract functions and gastrointestinal disorders.